OPTIMIZATION OF FERMENTATION CONDITIONS FOR PHYTASE PRODUCTION BY THE NOVEL ISOLATE KLEBSIELLA SP. - DAS, KAMALA; BANDYOPADHYAY , DEBASHIS; SUKANTA K. SEN, (The Bioscan, 2013)
Phytate is the main storage form of phosphorous of plant parts but it acts as antinutrients for the herbivores and certain aquatic animals. Since, it is present in bound form, its bioavailability depends mainly on the hydrolysis of phytate. In an attempt to screen phytase producing bacteria from aquatic soil environment, among 200 isolates on the basis of phytase production, SCTb2 strain was selected after primary and secondary screening. Following morphological, cultural and molecular characterization the isolate SCTb2 was identified as Klebsiella pneumoniae SCTb2. The environmental conditions, both physical and nutritional, were optimized for phytase production. The isolate could produce the phytase extracellularly in the shake flask condition. The maximum production of phytase by this isolate was observed after 72 hour incubation at 28°C and at pH 6.0. The best carbon and nitrogen sources for maximum phytase production were 1% sucrose and 0.1% ammonium nitrate, respectively.